Influence Entrepreneurial Marketing Against Success Business City Msmes Medan - Aditi, Bunga; Suyar, Annisha Suvero; Hasminidiarty, Hasminidiarty; Risal, Taufiq; Pratiwi, Henny (Program Pascasarjana STIE Amkop Makassar, 2023)
The purpose of this study is to identify, assess, and model the impact of entrepreneurial marketing on the success of MSME businesses in Medan City. This study used descriptive quantitative research as its methodology. In this study, the owners and managers of MSMEs in Medan City make up the population. 121 owners and managers of MSMEs in Medan City served as the study's samples, and the sample size was determined using the Hair et al formula and a straightforward random sampling technique. Using the IBM SPSS Statistics 26 program, multiple linear regression was used to evaluate the research data. According to the study's findings, entrepreneurial marketing and financing significantly and favorably influence MSME business success in Medan City. Keywords: Entrepreneurial Marketing, Capital, Business Success, MSMEs